School Principal's Leadership Strategy in Improving the Performance of PAI Teachers in the Digital Era: The Role of Learning Media and Motivation in Islamic Religious Teaching - Zia Ulhaq; Abdul Haris; Syamsurizal Yazid (Educazione: Journal of Education and Learning, 2025)
The main focus of this research is on the motivation provided by school principals, the development of teacher competencies through continuous training, and the use of learning facilities and media to support PAI teaching. The research method used is a qualitative approach with a case study design. The data collection technique was carried out through in-depth interviews with school principals and PAI teachers, direct observation of teaching practices, and analysis of documentation related to school policies. The collected data is then analyzed using thematic analysis techniques, which include data reduction, data display, and verification of findings. The results of the study show that the principal at MIS Muhammadiyah Darussalam Waioti has succeeded in creating a positive work environment by providing motivation in the form of formal and informal appreciation, as well as opening constructive communication channels with teachers. In addition, teacher competency development is carried out through continuous training and regular supervision, which focuses on improving pedagogical skills and the use of technology in teaching. The use of learning facilities and media, such as projectors and digital applications, has also been proven to improve the quality of PAI learning. The implications of this study show that school principals who implement transformative leadership strategies can improve the quality of teaching and teacher performance, which in turn contributes to improving the quality of Islamic religious education in schools